Printing protection of stickers of the alcoholic drinks - Вахлакова, Виктория Юрьевна; Бизюк, Андрей Валериевич (Eastern-European Journal of Enterprise Technologies, 2012)
Main reason of stable growth and high profitability of world polygraph market is a wide circle of users of products. Considerable part of market is made by a label. Its percent stake grows according to the world increase of population and increase of amount of commodities